Attitudes towards mother tongue education in Uganda: “you try to make sure that our children remain backward” - Becker, Julia Maximiliane (2014)
Mother tongue education is said to be best to the child. But what do parents and people involved think about this practice and its consequences? The paper investigates language attitudes towards mother tongue education in Uganda and provides a new perspective on educational language policies in Africa. Using language attitudes as heuristic enables to investigate people’s attitudes towards mother tongue education and argues that some approaches might be considered paternalistic.